The impact of controversial marketing in Nike stock price - Pimenta, Inês Jorge (2022)
Nike is widely known for its controversial marketing campaigns, which intend to give the company a competitive advantage in the market. In 2019, Nike spent $3.75bn in advertising and promotion costs compared to $3.58bn in 2018 and $3.34bn in 2017. Research shows that being the leading athletic brand comes with a cost, however, is this cost impacting the stock price positively or negatively? This work project analyzed the impact of five of the most controversial marketing campaigns Nike has ever released and evaluated their impact on the stock price. The conclusions were positive, the most relevant conclusion found was that controversial marketing campaigns are better perceived by the market when combined with endorsements and a strong positive social message.